Strategi bisnis lembaga penyiaran lokal pt bali ranadha televisi (bali tv) - Hermarani, Putu Arina; Gelgel, Ni Made Ras Amanda (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
Based on the KPID Bali website in 2020, PT Bali Ranadha Televisi is the first and only private local television broadcasting institution in Bali Province that is still active and persists in broadcasting local programs. The agency established a local television broadcasting station called Bali TV. The purpose of this study is to determine the business strategy of the local broadcaster PT Bali Ranadha Televisi. This qualitative research uses Niche Theory Analysis in Media Ecology. The results of this study are: 1) There are 6 types of local broadcast program content on Bali TV, 2) The target of audiences are from children to adults, 3) The capital used by Bali TV is human resources (HR), income from production costs of broadcast programs, advertising revenues, broadcast programs, and additional off-air programs, 4) Bali TV is referred to as a generalist media because it has various sources of life support.